Genotype-Independent Transformation and Genome Editing of Brassica napus Using a Novel Explant Material - Cao Chu, Uyen; Kumar, Sandeep; Sigmund, Amy; Johnson, Kari; Li, Yinghong; Vongdeuane, Pamila; Jones, Todd J. (Frontiers in Plant Science, 2020)
Agrobacterium-mediated transformation of canola (Brassica napus) via hypocotyl segments has been a commonly used method for the past 30 years. While the hypocotyl-based method is well-established, it is not readily adapted to elite germplasm and the prolonged process is not ideal for a production transformation setting. We developed an Agrobacterium-mediated transformation method based on epicotyl and higher stem (internodal) segments that is efficient, rapid, and amenable for high-throughput transformation and genome editing. The method has been successfully implemented in multiple canola genotypes. The method appears to be genotype-independent, with varying transformation efficiencies. Internodal segment transformation was used to generate transgenic events as well as CRISPR-Cas9-mediated frameshift gene knockouts.